PEMETAAN DAMPAK KERUSAKAN AKIBAT GEMPA BERDASARKAN MIKROTREMOR SEBAGAI USULAN PENATAAN WILAYAH KOTA - Nur Ayu Diana Citra Dewi S.P; Didik Purwanto (IST AKPRIND Yogyakarta, 2018)
The territory of Indonesia has long been known as a region with high seismic activity. This is due to the location of Indonesia which lies at the meeting of four major tectonic plates, namely the Euresia, Indo-Australian, Pacific and Philipine plates. The meeting of the plates resulted in tectonic mechanisms and the geological conditions of Indonesia becoming more complicated. Indonesia also has an island-arc structure with unique physiographic characteristics such as deep ocean trenches, geanticline belts, volcanic inner arcs, and marginal basins.Based on these conditions, it is necessary to analyze the earthquake zonation of Indonesia in the form of maximum acceleration of bedrock for the design of earthquake resistant seismic building with a certain risk. Assessment of vulnerable zones or the risk of earthquake damage in residential areas in Jember urban centers should be done carefully and systematically, in order to estimate the vulnerable building zones of damage can be known and studied.The results of this study, in the form of data processing from mikrotremor then made zonation map vulnerable damage during the earthquake. This map contains a zone that can be used as a place to develop settlements and zones that can not be developed according to the type of land and as a proposal to the municipality as a future arrangement of the area. In the study area has a low average VS value, which is about 50-300 m / s. It identifies that the subsurface layer in the study area is dominated by an alluvium sediment layer. This shows that some areas in Jember have soft soil conditions. Sub surface geological characteristics that cause damage to buildings where areas prone to damage to the northern part of the Research Area with low Vs and fo values is a soft soil type with large building damage occurring.